Pengembangan Media Pembelajaran Surprise Box Pada Materi Sistem Reproduksi Kelas IX SMPN Satap Katumbangan - Nur Adina Rizal; Dahlia Patiung; Ainul Uyuni Taufiq; Ummul Hasanah (Al-AHYA: Jurnal Pendidikan Biologi, 2022)
This development research aims to determine the level of validity, practicality, and effectiveness of Surprise Box learning media on the reproductive system material of class IX SMPN Satap Katumbangan. This research and development (R & D) referred to a 4-D development model consisting of four stages; define, design, develop, and disseminate. The subjects of this study were 13 students in class IX of SMPN Satap Katumbangan. The instruments in this study were literacy sheets, validation sheets, questionnaires, and learning outcomes tests. The media validation result is 3.8, which puts it in the "very valid" category. The assessment of responses through questionnaires of 91.25% is in the "very practical" category, and the student learning outcomes test is in the "effective" category because 100% of student learning outcomes were complete. This study implies that the Surprise Box learning media can make learning more effective, especially in reproductive system materials.